2016
DOI: 10.1111/os.12237
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Tumor Location, Nature and Bone Destruction of Extremity Osteosarcoma on Selection of Limb Salvage Operative Procedure

Abstract: Selection of limb salvage operative protocol for extremity OS should rely on tumor location, nature and extent of bone destruction. Regardless of tumor site, mechanical reconstruction is indicated for tumors with high invasion scores (>8), whereas biological reconstruction is preferred for those with low invasion scores (≤8). Tumors sparing the epiphyseal line or plate are ideal candidates for articular preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
(98 reference statements)
1
15
0
Order By: Relevance
“…We found that the MSTS limb function score in the joint preservation group was higher than that in the prosthesis replacement group, consistent with a previous study by Chen et al [15]. In their MSTS function evaluation of 90 osteosarcoma patients, the biological reconstruction and joint preservation scores (25.0 ± 3.3 and 25.1 ± 3.6) were signi cantly higher than the mechanical reconstruction and joint resection scores (23.4 ± 3.7 and 23.1 ± 3.4, P < 0.05).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that the MSTS limb function score in the joint preservation group was higher than that in the prosthesis replacement group, consistent with a previous study by Chen et al [15]. In their MSTS function evaluation of 90 osteosarcoma patients, the biological reconstruction and joint preservation scores (25.0 ± 3.3 and 25.1 ± 3.6) were signi cantly higher than the mechanical reconstruction and joint resection scores (23.4 ± 3.7 and 23.1 ± 3.4, P < 0.05).…”
Section: Discussionsupporting
confidence: 92%
“…In a recent study, Takeuch et al called it joint-preserving surgery (JPS) [11]. In the past decade, our team has been studying and improving this surgical approach [12][13][14][15], and because of the rise of the patient's age and the closure of the physis, we named it jointpreservation limb salvage.…”
Section: Discussionmentioning
confidence: 99%
“…The occurring rate was 4.0 (3.5–4.6) for 0–14 year-old children per year per million of people for males and females and from all ethnicities ( 1 ). Tumors arise primarily on the metaphysis, which is near the growth plate and gradually invade the epiphysis and eventually the whole joint space ( 2 ). The distal femur and proximal tibia are the most common sites for osteosarcomas, and the epiphyses of the distal femur and proximal tibia contribute ~35 and 30% to the growth of the lower extremity, respectively ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Musculoskeletal Tumour Society (MSTS) resection classification system [12], the defects were classified as S4 (4 patients), S5 (20 patients), S45 (3 patients) and S45E1 (one patient). Based on Mirel’s scoring system [13] and the invasion score for evaluating the extent of bone destruction through osteosarcoma [14], we made some improvements and proposed the bone strength scoring system. Five variables, including pain degree, tumor site, nature, length and transverse diameter, were utilized to evaluated the bone strength of the tumor segment (Table 2).…”
Section: Methodsmentioning
confidence: 99%